1997
DOI: 10.1007/bf02679955
|View full text |Cite
|
Sign up to set email alerts
|

A role for certain mouseAprt sequences in resistance to toxic adenine analogs

Abstract: A mouse embryonal carcinoma cell line hemizygous for the adenine phosphoribosyltransferase gene (aprt) was exposed to ultraviolet light (UV) or to the alkylating agent, ethyl methanesulfonate (EMS). Thirty eight cell lines retaining the aprt gene were isolated by selecting for resistance to 2,6-diaminopurine (DAP), an adenine analogue which selects against aprt activity. Of these, six cell lines distinguished by significant levels of aprt enzymatic activity after selection in DAP, were found to carry mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…These tandem events do not occur spontaneously in DNA repair-proficient cells (20). Tandem CC→TT events were induced by UV in the repair-proficient cells (16%) at frequencies consistent with previous studies (44). Surprisingly, most of the mutations (64%) induced by UV in the Pms2 null cells were tandem events, suggesting a role for Pms2 in suppressing these mutations when caused by UV damage.…”
Section: Oxidative Mutagenesis In Mmr-deficient Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…These tandem events do not occur spontaneously in DNA repair-proficient cells (20). Tandem CC→TT events were induced by UV in the repair-proficient cells (16%) at frequencies consistent with previous studies (44). Surprisingly, most of the mutations (64%) induced by UV in the Pms2 null cells were tandem events, suggesting a role for Pms2 in suppressing these mutations when caused by UV damage.…”
Section: Oxidative Mutagenesis In Mmr-deficient Cellssupporting
confidence: 88%
“…We found that 35% of mutant Aprt alleles from hydrogen peroxide-exposed Mlh1 null cells had two wellseparated base-pair substitutions, as compared with 9% of mutant alleles from untreated Mlh1 null cells (42). Only one base-pair substitution is required to eliminate Aprt expression (43,44), ruling out the possibility that both mutations were required for the selected phenotype. This result suggests that the induction of alleles with multiple mutations can be a signature for oxidative mutagenesis in MMR null cells.…”
Section: Oxidative Mutagenesis In Mmr-deficient Cellsmentioning
confidence: 81%
“…Different studies have shown that APRT participates in the purine salvage pathway in trypanosomatids by taking purines from the host and synthesizing them into nucleotides, since it catalyzes the conversion of free base adenine to AMP [Boitz and Ullman, 2006;Luscher et al, 2014]. This has been associated with resistance to toxic purine analogs in Trypanosoma brucei, Leishmania donovani, Saccharomyces cerevisiae, Drosophila melanogaster, and human cells [Johnson and Friedman, 1983;Woods et al, 1984;Kaur et al, 1986;Khattar and Turker, 1997]. However, no direct relationship has been found between APRT and the mechanisms of action and resistance to Bz in T. cruzi.…”
Section: Discussionmentioning
confidence: 99%